Nursing diagnoses for patients in the postoperative period of cardiac surgery - Carla Portolan Ribeiro; Caroline de Oliveira Silveira; Eliane Raquel Rieth Benetti; Joseila Sonego Gomes; Eniva Miladi Fernandes Stumm (Universidade Federal do Ceará, 2015)
Objective: to identify nursing diagnoses of patients in mediate postoperative period of cardiac surgery. Methods: descriptive, cross-sectional design with 26 patients in mediate postoperative period of cardiac surgery, in an intensive care unit. Data were collected through a form of socio-demographic/clinic characterization and nursing diagnoses. Results: one identified 15 risk nursing diagnoses and 34 real diagnoses, and the most common were related to the domain safety and protection. Conclusion: the identification of nursing diagnoses in patients after cardiac surgery allows one to direct nursing care and support appropriate interventions to individual needs, because patients in these conditions require immediate and accurate interventions.